The prevalence and efficacy of cross-training in a professional ballet environment: A literature review - Bonham, K. (University of South Carolina, 2021)
Fear of ruining the aesthetic integrity of the ideal "ballet body" once barred many dancers from cross-training for endurance and strength, but evidence suggests that these concerns are largely unsubstantiated, and several major dance companies have started integrating supplementary training into their class and rehearsal regimens. Ballet-specific risk factors, busy performance schedules, and the disparity between class and performance demands all limit the extent to which fitness training can be incorporated into professional environments. In addition, the applicability of objective technique analysis in subjective sports and a lack of reliable research within the population of interest have constrained the development of coordinated systems of care amongstmedical and artistic professionals. However, other sports set the standard for the future of a field which is progressing in the hands of pioneering experts across the globe. In this thesis, I will use a detailed literature review to outline the anticipated effects of a multifaceted cross-training program on the strength and endurance of professional ballet dancers and make suggestions for further research as it relates to the prevention of overuse injuries, the unique demands of ballet, and the periodization of training. These recommendations will be based upon the standards set by other sports as well as the opinions of current professionals who work within the confines of an emerging field.